Mechanical metamaterials with topologies based on curved elements: An overview of design, additive manufacturing and mechanical properties - Alberto Álvarez-Trejo; Enrique Cuan-Urquizo; Dhruv Bhate; Armando Roman-Flores (Materials & Design, 2023)
The design of metamaterials involves the optimal distribution of material inside a volume; therefore, it has benefited from the development of Additive Manufacturing (AM) techniques. Using AM allows the designer to create complex shapes including ones based on curved elements, which can take the shape of curved beams or minimal surfaces. Filling a space with repetitive patterns is not restricted to straight elements or struts, as not even nature solves all structural problems with them. Hence, curved elements have been widely used in metamaterial design, with potential applications in the biomedical, transportation, and packaging industries, among others. Mechanical metamaterials conformed with curved constituent elements are more flexible than those based on straight elements, which increases their energy absorption capacity while reducing stress concentration. The deformation mechanism of topologies with the same geometrical parametrization could be changed from stretch- to bending-dominated when modifying the specific parameter, e.g. increasing the curvature. The effective properties of curve based metamaterials have been studied by means of computational, analytical, and experimental approaches mainly based on standard compressive tests. An optimal distribution of material via parametric control of these topologies will lead to enhanced and customized mechanical properties.